A cognitive account of belief: a tentative road map - Connors, Michael H.; Halligan, Peter W. (Frontiers in Psychology, 2015)
Over the past decades, delusions have become the subject of growing and productive research spanning clinical and cognitive neurosciences. Despite this, the nature of belief, which underpins the construct of delusions, has received little formal investigation. No account of delusions, however, would be complete without a cognitive level analysis of belief per se. One reason for this neglect is the assumption that, unlike more established and accessible modular psychological process (e.g. vision, audition, face-recognition, language-processing, and motor-control systems), beliefs comprise more distributed and therefore less accessible central cognitive processes. In this paper, we suggest some defining characteristics and functions of beliefs. Working back from cognitive accounts of delusions, we consider potential candidate cognitive processes that may be involved in normal belief formation. Finally, we advance a multistage account of the belief process that could provide the basis for a more comprehensive model of belief.